ANALISA ALUR KERJA INSPIRASI DAN EKSPIRASI PADA ALAT VENTILATOR - Franedya Argarini Saragih; Hotromasari Dabukke (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2020)
Research has been carried out on the Hamilton C2 ventilator which aims to find out how the of inspiration and expiration are in accordance with what has been set on the ventilator by the operator or user. Installation of a ventilator is meant for patients who have excess or lack of oxygen within the lungs and who experience respiratory failure. Where the ventilator is a breathing apparatus that can help maintain ventilation and oxygen delivery for quite a long time.This research method is disbursed using qualitative and quantitative methods in order to collect data. Research on this ventilator was applied in several stages, namely setting and taking data that the ventilator on Volume Tidal (VT) must be in accordance with the Volume Tidal Expiratory (VTE) so there's no collapse within the patient and damage to the device itself. The results of this study are to determine the way of inspiration and expiration consistent with what has been set by observing the worth displayed on the Volume Tidal Expiratory (VTE) which is the same because the value that has been inputted within the Volume Tidal (VT. If the value displayed on the display or screen is <10% then there's a possibility of harm to the ventilator flow sensor or flow sensor within the patient, and the other way around if the value displayed on the display or screen is >10% then there's a possibility of injury to the flow sensors, both ventilator flow sensors and flow sensors within the patient.